An Efficient Cluster Authentication Scheme Based on VANET Environment in M2M Application - You-Boo Jeon; Keun-Ho Lee; Doo-Soon Park; Chang-Sung Jeong (International Journal of Distributed Sensor Networks)
Wireless and mobile sensor network technologies in M2M (machine to machine) are rapidly applied to our real life. Thus, in near future, advanced wireless and mobile sensor network in M2M application will be major key factor of the future generation convergence network which is based on the state of the application. It is expected that smart machines will appear as new business service model with other machines. Most numerous researches within M2M sectors are carried out in intelligent vehicle sector integrated with IT technology. Intelligent vehicle section shows severe changes in position between vehicles and has numerous large scales of networks in its components; therefore, it is required to provide safety by exchanging information between vehicles equipped with wireless communication function via VANET (vehicular ad hoc network) and fixed apparatus at roadside regarding the status of road. In this paper, we proposed cluster authentication scheme that mutually authenticates between vehicles by composing vehicle movement as cluster configuration architecture. We have successfully included the establishment of secure channels, the detection of replay attacks, mutual cluster authentication, prevention of vehicle identity fabrication, and secure distribution of provisional session key.